Pharmacokinetics and tolerability of eletriptan hydrobromide in healthy Korean subjects - Kim, Yu Kyong (Drug Des Devel Ther, 2018)
BACKGROUND: Migraine is one of the most common headache disorders that greatly affect the quality of life. Selective serotonin (5-HT) receptor agonists such as triptamine-based drugs called triptans are used for treatment of migraine. PURPOSE: This study aimed to evaluate the pharmacokinetic (PK) and tolerability profiles of eletriptan hydrobromide (eletriptan HBr), a selective 5-hydroxytryptamine (also known as serotonin) 1B/1D receptor agonist, in Koreans and compare the results to those observed in non-Koreans in a previously published study. PATIENTS AND METHODS: A randomized, open-label, single, and repeated-dose study was conducted in 16 healthy Korean male subjects using a four-treatment, four-period, and four-sequence crossover design (NCT01139515). The subjects received one of the following four treatments in each period: a single dose of 20, 40, 80 mg eletriptan HBr or a repeated oral dose of 40 mg 2 h apart. Blood samples were collected before and up to 26 h after dosing for quantification of plasma eletriptan concentration by high-performance liquid chromatography tandem–mass spectrometry. The PK parameters were estimated using noncompartmental methods. Ethnicity differences between Korean and non-Korean subjects were identified using geometric mean ratios and 90% confidence intervals (CIs) of dose-normalized maximum plasma concentration (C(max)) and dose-normalized area under the plasma concentration versus time curve from 0 h to the last measurable concentration (AUC(0–t)). RESULTS: After single-dose administration of eletriptan HBr to Korean subjects, the mean C(max) and AUC(0–t) increased linearly with dose. Comparable total systemic exposures were observed in the 2 h apart 40 mg repeated and single 80 mg dose. The geometric mean ratios (90% CIs) of the dose-normalized C(max) and AUC(0–t) of Korean subjects were similar to those of non-Korean subjects reported in the literature. The adverse events observed were transient and mild in severity. CONCLUSION: Eletriptan HBr showed linear PK and was well tolerated in Korean subjects. The PK and tolerability of eletriptan HBr did not differ between Korean and non-Korean subjects.